Detection of Adalimumab and Anti‐Adalimumab Levels by ELISA: Clinical Considerations. (November 2014) - Marinari, Barbara; Botti, Elisabetta; Bavetta, Mauro; Spallone, Giulia; Zangrilli, Arianna; Talamonti, Marina; Richetta, Antonio; Chimenti, Sergio; Costanzo, Antonio
Abstract: Enabling Technology, Genomics, Proteomics Clinical Development Phases I‐III Regulatory, Quality, Manufacturing Psoriasis (Ps) is a common and stigmatizing chronic inflammatory skin disease that may cause other chronic inflammatory conditions with overlapping pathology, such as rheumatoid arthritis (RA). Tumor necrosis factor (TNF) is a proinflammatory cytokine that plays a pivotal role in chronic inflammatory and autoimmune diseases such as uveitis, multiple sclerosis, systemic lupus, arthritis, Ps, and Crohn's disease. The TNF superfamily and receptors represent active targets for drug development. Anti‐TNF biological therapies, such as infliximab, adalimumab (ADL), and etanercept, are effective in treating RA, spondyloarthritis, Ps, and inflammatory bowel diseases, but long‐term treatment can induce anti‐drug antibody (ADA) formation associated with lower drug levels and clinical nonresponse. An investigation of the relationship between serum ADL/anti‐adalimumab antibody (AAA) concentration, and clinical response in moderate to severe Ps, confirmed an association between ADL and AAA levels and response. Although the detection of ADAs can be used to determine the cause of nonresponse and aid therapy decisions, the contrary observation of long‐term responders with low drug levels and detectable ADA suggests that another mechanism is also involved.